Белорусская русскоязычная драматургия после 2020 года: история травмы (на примере анонимных произведений) - Gulina, Anastasia (Slavia Orientalis, 2026)
After the protests of 2020, Belarusian theatre has been functioning under conditions of increasing censorship. Moreover, many theatre practitioners have been forced into exile, resulting in the emergence of the phenomenon of Belarusian theatre in exile. In this context, a number of playwrights, prioritizing their personal safety, have chosen to remain anonymous or publish their works under pseudonyms. This article, adopting the perspective of trauma studies, analyses three such plays, which makes it possible to identify several “painful points” within the current disintegration of Belarusian society and to understand the artistic means through which the authors attempt to overcome not only the recent traumatic experience of Belarusian society but also earlier ones, associated with such key historical events as the Chernobyl disaster and the collapse of the Soviet Union.